Marker-aided transfer of genes for B-Carotene biosynthesis into popular Philippine rice varieties - Alfonso, Antonio A.; Somera, Jean J.; Espejo, Emilie O.; Dilla, Christine Jade A.; Ravelo, Gerald B.; Garcia, Nelson S.; Avellanoza, Eleanor S. (2011)
Golden Rice accumulates B-carotene in the grains and is considered as a sustainable and effective food-based strategy to alleviate vitamin A deficiency. Through DNA marker-assisted recurrent backcrossing, Golden Rice1 (GR1) locus was introgressed into PSB Rc82 and NSIC Rc128 varieties. Selection in the progenies was based on yellow-colored dehulled grains after bleach treatment, presence of GR 1-specific PCR amplicons, high recovery of the recurrent parent genome, good agronomic traits and high betacarotene content. Parental recovery was measured using phenotypic data and polymorphic simple sequence repeat (SSR) markers (98 for PSB Rc82 and 103 for NSIC Rc128 progenies). After 2-3 backcrosses and 3-4 selfing generations, nine introgression lines (four from PSB Rc82 and five from NSIC Rc128) were selected. SSR data revealed at least 80% genomic recovery of the recurrent parents. The highest B-carotene concentration in the progenies using samples stored for two months at ambient temperature was 1.80 ug per gram of milled grains compared to 1.62 µgg in the GR donor. These results illustrate the feasibility of transferring Golden Rice trait into popular local varieties using this approach. Concomitant with the work on GRI was the introgression of Golden Rice2 event R (GR2-R, ~36 µg/g) into PSB Rc82. With higher betacarotene content, GR2-R will be used in line development, single- and multi-location field tests, biosafety and sensory evaluation, and other tests required for regulatory approval and varietal release. Activities towards combining GR2R with resistance to tungro and bacterial blight in elite genotypes are underway.
Keywords: Oryza sativa L; Rice varieties; Beta carotene